PEMODELAN MUKA AIR LAUT RERATA MENGGUNAKAN DATA SATELIT ALTIMETRI ENVISAT - Herry Risdianto (UNIVERSITAS INDO GLOBAL MANDIRI, 2016)
The purpose of this research was to create a model of Mean Sea Level (MSL). MSL modeling is done by determining Sea Surface Height (SSH) using Envisat altimetry satellite data with research sites in the sea south of Java. Evaluation is done by looking at the standard deviation of MLR models produced. The results showed that the standard deviation value 0 s.d. 0,999 m have the most amount of data, as many as 840 points, or about 94.49%. While the standard deviation value over 2 m have the least amount of data, as many as 18 points, or about 2.02%. While the remaining 3.49% is the standard deviation value between 1 s.d. 2 m.Keywords :MSL, SSH, Envisat.